Association of Plateletcrit Value with Gestational Diabetes Mellitus: A Case Control Study in A Tertiary Care Setting : Plateletcrit Value with Gestational Diabetes Mellitus - Chaudhary, Saima; Kausar, Zanjbila; Khan, Rodaba; Farhan, Eeshah (Pakistan Journal of Health Sciences, 2025)
Gestational Diabetes Mellitus (GDM) is linked to numerous maternal and fetal complications. Typically diagnosed in the third trimester with OGTT, early detection could prevent many adverse outcomes. Emerging evidence highlights the role of platelets in GDM pathogenesis, suggesting platelet indices, including plateletcrit, might aid early diagnosis. Objective: To determine the association between GDM and elevated plateletcrit levels. Methods: A case-control study was conducted over six months (May - October 2024) in Gynaecology and Obstetrics Unit 1, Sir Ganga Ram Hospital, Lahore. After ethical approval, 100 pregnant women meeting the inclusion criteria were enrolled. At 24–28 weeks’ gestation, all participants underwent a 75g OGTT. Based on results, they were divided into Group A (controls with normal OGTT) and Group B (cases with deranged OGTT). Plateletcrit values from the second trimester were obtained retrospectively from medical records. Quantitative variables were analyzed using Student’s t-test (P ≤ 0.05 deemed significant), while qualitative variables were expressed as percentages. Results: Group B (GDM patients) had significantly higher mean plateletcrit values (0.24 ± 0.08) compared to Group A (non-GDM) (0.14 ± 0.03) (P = 0.000). Conversely, the mean platelet count was higher in Group A than Group B (P = 0.000). Conclusion: Pregnant women with GDM exhibited higher plateletcrit values and lower platelet counts compared to non-GDM women, suggesting plateletcrit as a potential marker for early GDM diagnosis.